Deficit-Surplus and Firm Size on Capital Structure in Start-Up Companies Listed on the Indonesia Stock Exchange - Yatima Ayu Puspitasari; Mulyaningtyas (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study investigates the impact of financial deficit-surplus conditions and firm size on the capital structure of startup firms listed on the Indonesia Stock Exchange (IDX). The topic is relevant because startup funding fluctuations in 2023–2024 highlight the importance of balancing internal and external financing sources to sustain business operations. Background Problems: The research addresses the question: How do financial deficit-surplus conditions and firm size influence the capital structure of Indonesian startups, given the unique funding dynamics compared to traditional manufacturing firms? Research Methods: A quantitative approach was employed using multiple linear regression analysis. From an initial sample of 40 startups, 32 valid observations were analyzed after removing outliers. The data were drawn from IDX-listed startups, focusing on financial indicators and firm size. Finding/Results: The empirical results indicate that financial deficit-surplus conditions do not significantly affect capital structure, whereas firm size has a significant positive effect. This suggests that larger asset bases enable startups to secure external financing more effectively. Conclusion: The study concludes that capital structure in Indonesian startups is driven more by firm size and asset scale than by short-term financial conditions. The implication is that startups should prioritize strengthening assets and improving operational efficiency to maintain a stable and investor-attractive capital structure.